Determinants of breastfeeding discontinuation in an Italian cohort of mother-infant dyads in the first six months of life: a randomized controlled trial - Fabio Mosca; Paola Roggero; Francesca Garbarino; Daniela Morniroli; Beatrice Bracco; Laura Morlacchi; Domenica Mallardi; Maria Lorella Gianni; Dario Consonni (Italian Journal of Pediatrics, 2018)
Abstract Background Among breastfeeding determinants, the marketing of breast milk substitutes might contribute to suboptimal breastfeeding rates. The aim of this study was to investigate the effect of receiving information on breast milk substitutes on breastfeeding rates. Methods We conducted a randomized, single-blind, controlled trial from 2012 to 2014 in a northern Italian maternity ward. We enrolled 802 Caucasian mothers who gave birth to healthy, full-term singletons with a birth weight > 2500 g and who were exclusively breastfeeding from delivery to discharge. Mothers who gave birth to infants with congenital diseases, chromosomal abnormalities, perinatal infections and/or cardio-respiratory instability and/or mothers being affected by endocrine and/or metabolic and/or gastrointestinal and/or renal diseases were excluded. Mothers were randomized to either receive (group A, n = 405) or not (group B, n = 397) written information on a breast milk substitute at discharge. Breastfeeding was promoted and supported in all mother-infant pairs equally. The mode of feeding for up to 6 months after delivery was determined by phone interview. To detect a 10% difference between groups in the discontinuation rate of exclusive breastfeeding at three months of age at 5% significance and 80% power, a total of 356 mother-infant pairs per group were needed. Results The exclusive breastfeeding prevalence was 91% and 92% at 7 days, 79% and 70% at 1 month, 75% and 66% at 2 months, 72% and 62% at 3 months, and 3% and 2% at 6 months in groups A and B, respectively. The relative risk (95% confidence interval) of exclusive breastfeeding (group A vs B) at 7 days and at 1, 2, 3 and 6 months was as follows: 0.99 (0.95–1.03), 1.12 (1.03–1.21), 1.13 (1.03–1.24), 1.15 (1.04–1.27), and 1.49 (0.62–3.61). Nutritional, lifestyle and lactational factors were the primary contributing determinants to early breastfeeding discontinuation. Conclusions The present findings indicate that receiving written information on breast milk substitutes at hospital discharge, provided that breastfeeding support and education are offered, does not negatively affect breastfeeding rates. Trial registration NCT03208114. Registered 5 July 2017.